Generation of lower and upper bands of electrostatic electron cyclotron harmonic waves in the Van Allen radiation belts. Issue 11 (3rd June 2017) - Zhou, Qinghua; Xiao, Fuliang; Yang, Chang; Liu, Si; He, Yihua; Baker, D. N.; Spence, H. E.; Reeves, G. D.; Funsten, H. O.
Abstract: Electrostatic electron cyclotron harmonic (ECH) waves generated by the electron loss cone distribution can produce efficient scattering loss of plasma sheet electrons, which has a significant effect on the dynamics in the outer magnetosphere. Here we report two ECH emission events around the same location L ≈ 5.7–5.8, MLT ≈ 12 from Van Allen Probes on 11 February (event A) and 9 January 2014 (event B), respectively. The spectrum of ECH waves was centered at the lower half of the harmonic bands during event A, but the upper half during event B. The observed electron phase space density in both events is fitted by the subtracted bi‐Maxwellian distribution, and the fitting functions are used to evaluate the local growth rates of ECH waves based on a linear theory for homogeneous plasmas. ECH waves are excited by the loss cone instability of 50 eV–1 keV electrons in the lower half of harmonic bands in the low‐density plasmasphere in event A, and 1–10 keV electrons in the upper half of harmonic bands in a relatively high‐density region in event B. The current results successfully explain observations and provide a first direct evidence on how ECH waves are generated in the lower and upper half of harmonic frequency bands. Key Points: Initial data reported on two ECH wave events around the same location but in the different frequency band Numerical simulations show that ECH waves can be generated in the different half of harmonic frequency bands The background density and electron temperature are the main factors to yield the difference of wave spectrum